Removing the major allergen Bra j I from brown mustard (Brassica juncea) by CRISPR/Cas9. (2nd December 2021) - Assou, Juvenal; Zhang, Dingbo; Roth, Kristian D. R.; Steinke, Stephan; Hust, Michael; Reinard, Thomas; Winkelmann, Traud; Boch, Jens
SUMMARY: Food allergies are a major health issue worldwide. Modern breeding techniques such as genome editing via CRISPR/Cas9 have the potential to mitigate this by targeting allergens in plants. This study addressed the major allergen Bra j I, a seed storage protein of the 2S albumin class, in the allotetraploid brown mustard ( Brassica juncea ). Cotyledon explants of an Indian gene bank accession (CR2664) and the German variety Terratop were transformed using Agrobacterium tumefaciens harboring binary vectors with multiple single guide RNAs to induce either large deletions or frameshift mutations in both Bra j I homoeologs. A total of 49 T0 lines were obtained with up to 3.8% transformation efficiency. Four lines had large deletions of 566 up to 790 bp in the Bra j IB allele. Among 18 Terratop T0  lines, nine carried indels in the targeted regions. From 16 analyzed CR2664 T0  lines, 14 held indels and three had all four  Bra j I  alleles mutated. The majority of the CRISPR/Cas9‐induced mutations were heritable to T1 progenies. In some edited lines, seed formation and viability were reduced and seeds showed a precocious development of the embryo leading to a rupture of the testa already in the siliques. Immunoblotting using newly developed Bra j I‐specific antibodies revealed the amount of Bra j I protein to be reduced or absent in seed extracts of selected lines. Removing an allergenic determinant from mustard is an important first step towards the development of safer food crops. Significance Statement: Mustard is a significant elicitor of allergic reactions to food. The major allergen in brown mustard ( Brassica juncea ) is Bra j I, a 2S albumin seed storage protein. This is the first report of genome editing in B. juncea, and we mutated up to all four gene copies in this tetraploid plant resulting in plants with reduced levels or absence of Bra j I protein.